Manipulating concentrate level in the diet of tropical cattle to improve fiber utilization and mitigate greenhouse gas emissions - Mo, D.; Thu, N. V. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
This study evaluated the effects of concentrate level in diet, 10, 25, 40, and 60% forage dry matter (DM), on feed intake, nutrient utilization, weight gain (WG), and greenhouse gas (GHG) emissions in 12 male crossbred cattle (Red Sindhi × local, Bos indicus) 9-15 months of age in Southwestern Vi-etnam. The experiment was conducted for 6 months using a completely randomized block design. Ani-mals were individually housed and fed ad libitum with rice straw, with or without elephant grass, sup-plemented with commercial concentrate. Results showed that as the concentrate level increased, con-sumption of feeds, digestible nutrients and energy, WG, and GHG emissions rose linearly (P < 0.01), whereas neutral detergent fiber (NDFD) and acid detergent fiber digestibility declined (P < 0.05). The DM, organic matter, and crude protein digestibility were not significantly affected (P > 0.05). The in vitro NDFD assessments exhibited similar trends to the in vivo data (R² > 0.75). GHG emissions per unit of live weight were significantly reduced (P < 0.01) as concentrate levels increased up to 60%, alt-hough the difference between the 40% and 60% groups was not statistically significant (P > 0.05). These findings suggest that a concentrate level of 40% forage DM offers an optimal balance between fiber utilization and GHG emission intensity. The in vitro technique using rumen fluid from slaugh-tered cattle with unknown dietary history and minimized chemical reagents may serve as a practical and ethical tool for evaluating fiber utilization in cattle nutrition studies.